The Role of Management Information Systems in E-Commerce Business on Shopee - Dewi Puspaningtyas Faeni; Kanizah Kanizah (Universitas 45 Surabaya, 2024)
This research aims to determine the role of management information systems in the e-commerce business on Shopee. In the era of globalization, technological developments have had an impact on business progress, including e-commerce. Shopee as an online e-commerce application requires a strategy to increase customer loyalty and increase competitiveness in the e-commerce industry. This research uses qualitative methods with a descriptive approach and literature study methods. The research results show that technological developments have led to very efficient business growth, where businesses can now be launched through e-commerce. Shopee has its own unique features and advantages that enable the company to run smoothly and successfully. With increasingly rapid advances in technology, it is hoped that Shopee can utilize technology effectively and most importantly for its users, Shopee has the ability to update its applications or websites so as not to influence events that have occurred in the past.